Method to Protect Charge Recombination in the Back-Contact Dye-Sensitized Solar Cell - Yoo, Beomjin; Kim, Kang-Jin; Lee, Doh-Kwon; Kim, Kyungkon; Ko, Min Jae; Kim, Yong Hyun; Kim, Won Mok; Park, Nam-Gyu (OPTICAL SOC AMER, 2010)
We prepared a back-contact dye-sensitized solar cell and investigated effect of the sputter deposited thin TiO2 film on the back-contact ITO electrode on photovoltaic property. The nanocrystalline TiO2 layer with thickness of about 11 mu m formed on a plain glass substrate in the back-contact structure showed higher optical transmittance than that formed on an ITO-coated glass substrate, which led to an improved photocurrent density by about 6.3%. However, photovoltage was found to decrease from 817 mV to 773 mV. The photovoltage recovered after deposition of a 35 nm-thick thin TiO2 film on the surface of the back-contact ITO electrode. Little difference in time constant for electron transport was found for the back-contact ITO electrodes with and without the sputter deposited thin TiO2 film. Whereas, time constant for charge recombination increased after introduction of the thin TiO2 film, indicating that such a thin TiO2 film protected back electron transfer, associated with the recovery of photovoltage. As the result of the improved photocurrent density without deterioration of photovoltage, the back-contact dye-sensitized solar cell exhibited 13.6% higher efficiency than the ITO-coated glass substrate-based dye-sensitized solar cell. (C) 2010 Optical Society of America
Keywords: CONVERSION EFFICIENCY; LOW-COST; TRANSPORT; GEOMETRY